2010
DOI: 10.1159/000313654
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Value of Absolute Lymphocyte Counts before Bortezomib-Dexamethasone Therapy in Relapsed Multiple Myeloma Patients

Abstract: A high absolute lymphocyte count (ALC) at diagnosis is known as a surrogate marker of favorable prognosis in newly diagnosed multiple myeloma (MM). Recent studies showed tumor sensitization and enhanced cytotoxicity of bortezomib. We hypothesized that a high ALC before bortezomib treatment would contribute to tumor sensitization and activated cytotoxicity of bortezomib in relapsed MM. Ninety-seven relapsed MM patients who underwent bortezomib-dexamethasone (Vel-Dex) therapy were analyzed. Median follow-up dura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 47 publications
1
4
0
Order By: Relevance
“…Although ALC did not have statistical significance in multivariate analysis due to the relatively small sample size, our results are in agreement with previous reports showing that a high ALC is associated with better prognosis in newly diagnosed MM (cut-off point, 1,400 cells/µL; the same as that used our study),3 relapsed MM after Vel-Dex therapy (cut-off point, 1,100 cells/µL)23 and other lymphomas 24…”
Section: Discussionsupporting
confidence: 92%
“…Although ALC did not have statistical significance in multivariate analysis due to the relatively small sample size, our results are in agreement with previous reports showing that a high ALC is associated with better prognosis in newly diagnosed MM (cut-off point, 1,400 cells/µL; the same as that used our study),3 relapsed MM after Vel-Dex therapy (cut-off point, 1,100 cells/µL)23 and other lymphomas 24…”
Section: Discussionsupporting
confidence: 92%
“…It has also been reported that the levels of CD19 + and naive CD4 + cells can distinguish between subgroups of MM patients based on survival and that decreased level of CD4 + cells in the marrow lymphocyte population correlates with progressive disease [4]. This correlation was also found during the course of the disease, after two years of therapy, or in relapsed MM patients [10]. Patients with higher level of CD19 + cells were also found to have decreased incidence, severity, and mortality from infections [11].…”
mentioning
confidence: 84%
“…Retrospective studies in MM have shown that a higher ALC before bortezomib therapy is associated with better overall survival (OS). 10 Furthermore, in MM patients undergoing autologous stem cell transplant (ASCT), both higher pre-ASCT ALC levels and early post-ASCT recovery of ALC were independent prognostic factors for OS. 11 Taken together, the ratio of ALC to AMC may represent the relative strength of the host immune system (that is, ALC) to tumor-induced immune dysfunction (that is, AMC, reflective of TAMs).…”
mentioning
confidence: 99%